2021
DOI: 10.1371/journal.pone.0258905
|View full text |Cite
|
Sign up to set email alerts
|

Foods from the wild: Local knowledge, use pattern and distribution in Western Nepal

Abstract: Locally harvested wild edible plants (WEPs) provide food as well as cash income for indigenous peoples and local communities, and they are of great importance in ensuring local food security. However, their uses and availability are poorly documented. This study aimed to enumerate WEP diversity and status of WEPs in a part of the Annapurna Conservation Area, Sikles region, where the population is dominated by the Gurung community. Ethnobotanical data were collected using guided field walks, semi-structured int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 58 publications
5
15
0
Order By: Relevance
“…Notably, age groups had a significant association with indigenous knowledge of WEFs. In this regard, we found high indigenous knowledge among middle-aged people in their 40s and 50s compared to younger and older age groups, which are consistent with studies done in Pakistan and Nepal [ 39 , 62 ]. However, it contradicts the findings of Uprety et al [ 21 ] where younger people were more knowledgeable than the older population, and some studies in China where the oldest generation had more traditional knowledge than others [ 55 , 63 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Notably, age groups had a significant association with indigenous knowledge of WEFs. In this regard, we found high indigenous knowledge among middle-aged people in their 40s and 50s compared to younger and older age groups, which are consistent with studies done in Pakistan and Nepal [ 39 , 62 ]. However, it contradicts the findings of Uprety et al [ 21 ] where younger people were more knowledgeable than the older population, and some studies in China where the oldest generation had more traditional knowledge than others [ 55 , 63 ].…”
Section: Discussionsupporting
confidence: 91%
“…On the contrary, Kang et al [ 67 ] concluded that men were more knowledgeable in Central China. Similarly, studies from Nepal and Argentina also reported that men identified more fruit species than women [ 62 , 68 ]. These three studies were conducted in communities with rich forest cover where it was always the men who ventured further into the forest.…”
Section: Discussionmentioning
confidence: 94%
“…Documenting traditional knowledge and practices is also crucial for establishing medicinal plant management and conservation programs (Njoroge et al 2004). Plant resources are still being used in many regions of Nepal to fulfill subsistence requirements or to market as edible fruits, vegetables, fodder, medicinal herbs, and raw materials for home construction and domestic products, according to a large number of ethnobotanical studies published in Nepal (Manandhar 1989, Bhattarai et al 2006, Rokaya et al 2010, Uprety et al 2010, Bhattarai 2018, Kunwar et al 2018, Pradhan et al 2020, Mallik et al 2020, Khakurel et al 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Garibay-Orijel et al [ 71 ], who reviewed 80 ethnomycological studies, also reported a greater role of women worldwide in mushroom collection, processing, and marketing. However, some studies carried out in Poland [ 58 , 72 ], China [ 61 ], and Africa [ 73 – 75 ] have reported that men are significantly more knowledgeable regarding WEM than women as they can move deep into the forest without any fear [ 76 ], whereas few others [ 77 , 78 ] say that, there is no significant difference between the genders vis - a - vis knowledge of WEM.…”
Section: Discussionmentioning
confidence: 99%